The New Cold War in the Middle East: Iran–Russia Strategic Alignment and U.S. Policy Challenges - Hasnain Abbas*; Zahid Hussain (Dialogue Social Science Review (DSSR), 2025)
Since the mid-2010s, and accelerated by the 2022 Russian invasion of Ukraine and renewed tensions between Tehran and Washington, Iran and Russia have deepened strategic ties across military, energy, political, and economic domains. What looks increasingly like a “new Cold War” in parts of the Middle East pits a Moscow–Tehran axis (tactical, transactional, and growingly institutionalized) against persistent but recalibrating U.S. interests in regional stability, containment of adversaries, and support for partners. This paper examines drivers of Iran–Russia alignment, key arenas of cooperation (Syria, energy, military-technical exchange), limits to the partnership, and the strategic dilemmas this presents for U.S. policy. The paper concludes with actionable U.S. policy recommendations that mix deterrence, targeted engagement, alliance building, and resilience measures for regional partners. Keywords: Iran, Russia, Middle East, U.S. policy, strategic alignment, energy, military cooperation, Syria